Knowledge and practice of airborne and droplet precautions among healthcare students during COVID-19 pandemic - Khalifa Binkhamis; Mazin Barry; Mashel K Alkahtani; Rakan J Almetary; Dana A Alrasheed; Abduljabbar A Alyamani; Maha M Barakeh (Wolters Kluwer Medknow Publications, 2022)
Background: Health-care workers are at risk of contracting and transmitting infections. Few studies have assessed knowledge of transmission-based precautions during the COVID-19 pandemic. The aim of this study is to estimate the students' knowledge and practice of airborne and droplet precautions as well as knowledge of COVID-19 measures among medical, dental, and nursing students at King Saud University (KSU) during the COVID-19 pandemic. Subjects and Methods: This was a cross-sectional survey-based study conducted from August 2020 to October 2020 at KSU. Students that met the inclusion criteria were contacted and given questionnaires through social media; a convenience sampling technique was implemented due to limitations of contact during the pandemic. Results: 435 students were included in the study. Most of them were females (61.4%), and the distribution was 31.7%, 25.5%, and 42.8% for medical, dentistry, and nursing students, respectively. The mean knowledge of airborne and droplet precautions was 56.6%. Nursing and dentistry students displayed significantly lower knowledge of isolation precautions compared to medical students (P < 0.001). Knowledge of isolation precautions had correlated significantly and positively with self-rated better hygienic practices, r = 0.340, P < 0.010. The students' average knowledge score about COVID-19 was 81.37%. Moreover, results showed that students' overall mean willingness to take the vaccine for COVID-19 was 81%. Students' mean self-rated willingness to undergo COVID-19 vaccination correlated significantly and positively with their knowledge of infection control (r = 0.162, P < 0.010). Conclusion: Based on our study, the overall mean knowledge and practice of KSU health students were satisfactory, and their willingness to vaccinate against COVID-19 is acceptable. The study took place while students were learning online hence, we suggest future research to examine the practice of infection control measures after the pandemic.